The Quality of Competence Through Nursing Career Paths Among Indonesian Nurses in Hospital Settings - Muhammad Hadi; Dina Rahmawati; Nyimas Heny Purwati; Dhea Natashia; Slametiningsih Slametiningsih; Idyatul Hasanah (Journal of Public Health and Pharmacy)
ntroduction: Nurses play a pivotal role in the provision of healthcare services both within the Indonesian context and on a worldwide scale. The development of nursing competence is crucial in order to guarantee the provision of high-quality healthcare services. To examine the elements that are linked to the enhancement of nurse competence by means of the adoption of nursing career paths within hospital settings in Indonesia.